Aura in temporal lobe epilepsy: correlation with postsurgical outcome - Milenković, Jana; Vojvodić, Nikola (Medicinski podmladak, 2022)
Introduction: Aura is subjective feeling that represents warning of the incoming seizure and it is the very beginning of the epileptic seizure. Epilepsy is chronical disease which manifests itself through spontaneous repetition of epileptic seizures. Aim: Determine the differences between characteristics of auras in patients with pharmacoresistant temporal epilepsy which were in remission after the surgically treatment and patients who had recurrent seizures after the procedure. Material and methods: This is a retrospective study of the pharmacoresistance epilepsy patients treated in the Neurology Clinic, Epilepsy Department, Clinical Center of Serbia in the period between July 1, 2010 and June 30, 2019 who were treated by resective surgical treatment and were postoperatively tracked for one year. The information that were collected were about the duration of epilepsy, the presence of febrile seizures, lateralization of the ictal and interictal EEG, and number and type of the auras that patients had. Chi-square and Fisher’s test will be used in order to asses the difference in frequency between examined variables according to postsurgical outcome. Statistical method will be considered as significant if p≤0,05. Analysis done in , IBM SPSS ver. 21”. Results: Total number of the patients in this study is 132, 57 male and 75 female. The most common type of the aura was mesial temporal aura and it was present in 77 (58.3%) patients, and after that by frequency comes nonspecific aura(12.1%). 50% of the patients had only one aura, and 17(12.9%) patients were without auras. 110 patients had favorable outcome, and 22 patients had non-favorable outcome. There was no statistically significant difference found at frequency of examined variables according top postsurgical outcome. (p>0.05). The statistically significant difference in localization of the interictal EEG according to epileptic focus was discovered (p<0.001). Conclusion: There is no statistically significant difference in frequency of listed variables according to outcome.